2018
DOI: 10.1139/apnm-2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term exposures to low iron and branched-chain amino acid containing diets on aging skeletal muscle of Fisher 344 × Brown Norway rats

Abstract: Aging skeletal muscle displays an altered iron status that may promote oxidative stress and sarcopenia. A low iron (LI) containing diet could reduce muscle iron status and attenuate age-related muscle atrophy. Supplemental branched-chain amino acids (BCAA) may also alleviate sarcopenia by promoting muscle protein synthesis and iron status improvement. This study examined individual and combined effects of LI and BCAA diets on anabolic signaling and iron status in skeletal muscle of aging rats. Twenty-nine-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…On the other hand, supplementation with BCAAs can also improve aging by promoting muscle protein synthesis and iron content ( 23 ), and BCAA supplementation significantly inhibits the decrease in serum albumin in elderly patients compared with that in young patients ( 24 ). In addition, BCAA supplementation can promote wound healing, reduce the occurrence of kidney and liver diseases with age ( 25 ), and reduce inflammatory markers in patients with chronic heart failure ( 26 ).…”
Section: Bcaas and Lifespanmentioning
confidence: 99%
“…On the other hand, supplementation with BCAAs can also improve aging by promoting muscle protein synthesis and iron content ( 23 ), and BCAA supplementation significantly inhibits the decrease in serum albumin in elderly patients compared with that in young patients ( 24 ). In addition, BCAA supplementation can promote wound healing, reduce the occurrence of kidney and liver diseases with age ( 25 ), and reduce inflammatory markers in patients with chronic heart failure ( 26 ).…”
Section: Bcaas and Lifespanmentioning
confidence: 99%
“…In addition, an increase in both BCAAs and Arg in the diet could have a synergetic effect by means of activating the target of rapamycin complex (mTOR) cell signalling [5]; in fact, in rats, BCAAs can inhibit the catabolism of Arg in the mammary tissue and increase its availability [22], therefore, the increased availability of Arg would increase the synthesis of nitric oxide which acts as a major vasodilator increasing the blood flow and, in turn, the uptake of nutrients [5,17]. However, to the authors' knowledge, no study has investigated this potential synergic effect between BCAAs and Arg.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies suggested a possible link between BCAAs, mTORC1 and hematological parameters (9)(10)(11). Significant increases in hemoglobin (Hb), serum iron, red blood cell count and hematocrit were observed in a small cohort of 23 athletes after a 90-day administration of a BCAAmixture (9).…”
Section: Introductionmentioning
confidence: 99%